From maecenate to cultural marketing: the evolution of sponsorship in Brazil - Correia, Inês Fernandes (Organicom, 2010)
The paper identifies the moments when sponsorship was crucial for the development of culture and of communication. It seeks to demonstrate that this activity was once conducted with amateurism and individuality and today is governed by marketing actions. The journey begins in Imperial Brazil, reaching modernity to map out the characters or institutions that are responsible for encouraging artistic and cultural production, while stressing the importance that cultural marketing has gained for artistic and media-related accomplishments.